The Use of Lung Ultrasound Rather than Chest X-Ray to Diagnose Neonatal Lung Disease: Time for Action - Jing Liu; Peng Jiang (Diagnostics, 2025)
Traditionally, the diagnosis of lung diseases has primarily relied on chest X-ray (CXR) or even CT examination results, which are considered the “Gold Standard” for lung disease diagnosis; in comparison, lung ultrasound (LUS) is considered a “forbidden zone” for diagnosing lung diseases [...]